Predictors and clinical implications of atrial fibrillation in patients with severe aortic stenosis undergoing transcatheter aortic valve implantation. Issue 3 (30th October 2014) - Barbash, Israel M.; Minha, Sa'ar; Ben‐Dor, Itsik; Dvir, Danny; Torguson, Rebecca; Aly, Muhammad; Bond, Elizabeth; Satler, Lowell F.; Pichard, Augusto D.; Waksman, Ron
<x xml:space="preserve">Abstract</x> Objectives To assess the prevalence at baseline, postprocedural incidence, and clinical impact of atrial fibrillation (AF) on consecutive patients undergoing transcatheter aortic valve implantation (TAVI). Background AF in patients with aortic stenosis (AS) is an independent risk factor for adverse outcome. Despite the evidence for high AF prevalence and the increased risk in surgical series, there are limited data with regard to AF and its impact on outcome after TAVI. Methods Consecutive patients with symptomatic, severe AS were analyzed and categorized according to prevalence of AF on initial admission (baseline AF) and according to the development of new AF postprocedure (postprocedure AF). A total of 371 patients were included in the analysis; of them, 143 (39%) had AF at baseline. Results No difference in procedural and hospital outcome was found between groups; however, baseline AF patients did have higher 1‐year mortality (28.8 vs. 18%, P = 0.01). Of the patients with no baseline AF, 46 patients (20%) developed new, postprocedural AF during their hospital stay. Inhospital death was twice as frequent in patients with new, postprocedure AF, however, this difference did not reach statistical significance (13 vs. 6.7%, P = 0.22). Procedure hemodynamic instability (OR 9.3; 95% CI 1.5–59), and transapical access (OR 4.96, 95% CI 1.9–13.2) were independent predictors for development of new AF. Conclusions Baseline and postprocedure AF are common in AS patients undergoing TAVI. However, only postprocedure AF is associated with a prolonged and more complicated hospital course. AF is associated with poor long‐term, but not short‐term, mortality. © 2014 Wiley Periodicals, Inc.